Exchange Rate Pass-Through and Dynamic Oligopoly : An Empirical Investigation - Gross, Dominique (IMF Working Papers; Working Paper ;, 1999)
This paper explicitly takes into account the dynamic oligopolistic rivalry among source producers to evaluate the degree of exchange rate pass-through. Using recent time-series techniques for the case of imported automobiles in Switzerland, the results show that prices are strategic complements and that the degree of pass-through is lower in the long run than in the short run. We attribute this to the fact that, although some rivals match long-term price changes, others do not, inducing the producer who faces a change in exchange rate to absorb a greater proportion of the variation.